Elucidating biofilm diversity on water lily leaves through 16S rRNA amplicon analysis: Comparison of four DNA extraction kits. (28th August 2021) - Janssen, Kathrin; Low, Shook Ling; Wang, Yan; Mu, Qi‐Yong; Bierbaum, Gabriele; Gee, Carole T.
Abstract: Premise: Within a broader study on leaf fossilization in freshwater environments, a long‐term study on the development and microbiome composition of biofilms on the foliage of aquatic plants has been initiated to understand how microbes and biofilms contribute to leaf decay and preservation. Here, water lily leaves are employed as a study model to investigate the relationship between bacterial microbiomes, biodegradation, and fossilization. We compare four DNA extraction kits to reduce biases in interpretation and to identify the most suitable kit for the extraction of DNA from bacteria associated with biofilms on decaying water lily leaves for 16S rRNA amplicon analysis. Methods: We extracted surface‐associated DNA from Nymphaea leaves in early stages of decay at two water depth levels using four commercially available kits to identify the most suitable protocol for bacterial extraction, applying a mock microbial community standard to enable a reliable comparison of the kits. Results: Kit 4, the FastDNA Spin Kit for Soil, resulted in high DNA concentrations with better quality and yielded the most accurate depiction of the mock community. Comparison of the leaves at two water depths showed no significant differences in community composition. Discussion: The success of Kit 4 may be attributed to its use of bead beating with a homogenizer, which was more efficient in the lysis of Gram‐positive bacteria than the manual vortexing protocols used by the other kits. Our results show that microbial composition on leaves during early decay remains comparable and may change only in later stages of decomposition.